Synthesis of triblock copolymer of polycaprolactone and polylysine - Chen, Zhao (Nanyang Technological University, 2020)
Polypeptide copolymers are a promising candidate that plays an important role in biomedical realms, such as drug delivery, gene transfer, biomedical devices, and consumer products. For combating a multidrug resistant bacterium, a peptide-based cationic block copolymer attracts widespread attention mainly because of the ease and low cost of production as well as the diversity in design and functionality. As an ideal biomimetic alternative for antimicrobial peptides (AMPs), polypeptide copolymers are mostly synthesized through the ring-opening polymerization (ROP) of amino-acid N-carboxyanhydride (NCAs), and their properties can be tuned by controlling the block sequence, composition, secondary structure, and overall molecular weight and polydispersity. During this study, we synthesized a series of ABA type triblock copolymers (pKnC40Kn), namely, poly(lysine-b-caprolactone-b-lysine). The target products were successfully made, as supported by the characterization of 1H-NMR, 13C-NMR and Dimethylformamide Gel Permeation Chromatography (DMF GPC). The formation of quasi-micrometer particles is created by the self-assembly of the amphiphilic pKnC40Kn via a nanoprecipitation method and varying the length of lysine units. Different morphologies such as micelle, vesicle, rod, and worm-like are observed by TEM. By using DLS analysis and zeta-potential measurements, the hydrodynamic radius of these quasi-micrometer particles ranges from 182.4 nm to 1025 nm, and the surface charge stays highly positive above 40 mV. The bioassay indicates that the pKnC40Kn has a moderate biocide efficacy against E. coli and MRSA and a superb biocompatibility at 62.5 ppm. Intriguingly, after the encapsulation of thymol, the quasi-micrometer particles perform a noticeable synergistic effect against Gram-positive methicillin-resistant Staphylococcus aureus (MRSA) with a 16-times improvement in biocidal efficacy.